STUDY CORRELATION BETWEEN BURDEN AND QUALITY OF LIFE OF DEPENDENT ELDERLY CAREGIVERS IN KLITREN, YOGYAKARTA - Kristina, Hana; Widagdo, The Maria Meiwati; Perdamaian, Teguh Kristian (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2022)
Introduction:Â Elderly with disability need caregiverâ€™s assistance in their activities of daily living. The caregiver can experience burden during caring for dependent elderly. The burden can affect caregiverâ€™s quality of life.Objectives: to measure and test the correlation between dependent elderlyâ€™s caregiver burden and quality of life in Klitren Kampong, Gondokusuman District, Yogyakarta Municipality.Â Materials and Methods:Â Â The subjects were primary informal caregivers aged â‰¥ 18 years with good cognitive functions who caring for the elders with ADL score <12. Respondents were selected using consecutive sampling technique. This is a quantitative research with cross-sectional study design. Zarit Burden Interview and Caregiver Reaction Assessment were used to assessing caregiverâ€™s burden. WHO Quality of Life-BREF was used to assess caregiverâ€™s quality of life. Data was analysed using spearmanâ€™s rank correlation.Â Results:Â There were 21 female study subjects. In each of the CRA and ZBI domains, the caregiversâ€™ burden tend to be low (mean=8.63Â±10.730â€“72.42Â±10.983). Caregiversâ€™ quality of life tend to be low (mean=49.76Â±11.962â€“60.76Â±11.726). There is a strong and statistically significant correlation between the impact on finance (p=0.000, Ï=-0.678) and impact on health (p=0.002, Ï=-0.602) domain on CRA with the environmental domain of WHOQoL-BREF. There is a strong and statistically significant correlation between the impact on schedule domain on CRA with the psychological domain of WHOQoL-BREF (p=0,000, Ï=-0.683).Â Conclusion:Â There are significant correlations between caregiversâ€™ burden and quality of life especially on certain domains. Caregivers with higher burden have lower quality of life.